Preparation process of fast-charging negative electrode material
Through the composite of modified graphite and silicon material and the addition of nanocarbon, a high specific capacity silicon-carbon composite fast-charge anode material was prepared, which solved the problem of insufficient performance of existing graphite and silicon anode materials in fast charging and discharge lithium-ion batteries, and achieved high energy density and excellent conductivity.
Patent Information
- Application Number
- CN202411963380.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-12-30
AI Technical Summary
Existing graphite negative electrode materials show poor high-current charging and discharging performance in fast charging and discharging lithium-ion batteries, and the silicon negative electrode materials have severe volume expansion and contraction and poor electronic conductivity during charging and discharging, which limits its development.
By controlling the graphite preparation process, the material is modified using nanocarbon, and the modified graphite material is composited with silicon material to prepare a high specific capacity silicon-carbon composite fast-charge negative electrode material. This material improves the conductivity and cyclic stability of the material through asphalt coating and the addition of carbon nanotube conductive agent.
It achieves high energy density, excellent conductivity, good cycle stability and high specific capacity, meets the needs of fast charging and discharging lithium-ion batteries, and improves the charging and discharging performance of silicon-carbon materials.
Smart Images

Figure CN119764400A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a new material, and in particular to a preparation process of a fast-charging negative electrode material. Background Art
[0002] At present, although graphite negative electrode materials have high specific capacity and stable cycle performance, their large current charge and discharge performance is relatively poor, which limits the development of new application areas. Therefore, the development of negative electrode materials that can adapt to fast charging and discharging of lithium-ion batteries is the key to maintaining graphite's dominant position in the field of negative electrode materials. In addition, the specific capacity of graphite materials is currently close to the theoretical specific capacity. Therefore, the development of new negative electrode materials with high specific capacity to meet the needs of new high-energy density lithium batteries is also an important development direction for negative electrode materials. Silicon negative electrodes have extremely high theoretical specific capacity and relatively stable materials, but silicon negative electrodes are often accompanied by severe volume expansion and contraction during the charging and discharging process, and have poor electronic conductivity, which greatly limits their development in the field of negative electrode materials.
[0003] The present invention is based on the consideration of the above problems. By controlling the graphite preparation process and modifying the material with nano-carbon, a graphite negative electrode material with excellent rate and cycle performance is obtained, and it is compounded with silicon material to obtain a new type of negative electrode material with high specific capacity, and has the following characteristics: (1) high energy density; (2) excellent conductivity; (3) good cycle stability; (4) excellent specific capacity. The silicon-carbon composite fast-charging negative electrode material is a composite of silicon and carbon, combining the high energy density of silicon with the good conductivity and structural stability of carbon. The negative electrode materials in the prior art are mainly modified natural graphite and artificial graphite. Although the technology is mature, the theoretical specific capacity is limited. The theoretical specific capacity of the silicon-carbon composite negative electrode material is much higher than that of the graphite negative electrode material in the prior art, and can provide higher energy density to meet the demand of consumer electronic products for longer battery life. Summary of the invention
[0004] In view of the above problems, the present invention provides a preparation process of a fast-charging negative electrode material.
[0005] The present invention provides a preparation process for a fast-charging negative electrode material, comprising the following steps: preparation of an intermediate phase asphalt, preparation of an artificial graphite material, preparation of asphalt-coated silicon-carbon composite particles, preparation of a carbon nanotube conductive agent, preparation of a glucose-based hard carbon precursor, and preparation of a silicon-carbon composite fast-charging negative electrode material.
[0006] Wherein, the preparation of the glucose-based hard carbon precursor in step (5) comprises:
[0007] Glucose and water are mixed to obtain a glucose solution, and then the glucose solution and water are added into a stainless steel high-pressure reactor, and after hydrothermal reaction at a certain temperature, the mixture is naturally cooled to room temperature, washed with deionized water and filtered to neutrality, and the obtained solid precipitate is dried in a forced air drying oven to obtain a glucose-based hard carbon precursor;
[0008] Step (6) Preparation of silicon-carbon composite fast-charge negative electrode material includes:
[0009] The glucose-based hard carbon precursor of step (5) is added to the asphalt-coated silicon-carbon composite material of step (3) for coating, and finally the carbon nanotube conductive agent of step (4) is added and sintered in a tube furnace (after heating, the precursor is pre-carbonized at medium and low temperature, then heated, kept warm, ground and sieved to obtain a silicon-carbon composite fast-charging negative electrode material.
[0010] Preferably, in step (1), the preparation of mesophase asphalt is
[0011] After the raw material asphalt is ground and crushed, a thermal conversion experiment is carried out in a stainless steel high-temperature and high-pressure reactor equipped with a temperature controller. Under the protection of N2 atmosphere, the system is pressurized, stirred, kept at a constant temperature for a certain period of time, the system pressure is discharged, and the system is naturally cooled to room temperature to obtain the intermediate phase asphalt.
[0012] Step (2) Preparation of artificial graphite material
[0013] Take needle coke powder, add the mesophase pitch of step (1) thereto, mix the two thoroughly and evenly in a VC mixer, stir for a certain time, set the frequency, place the mixture in a homemade converter under N2 protection for granulation, heat it to a specified temperature at a certain heating rate, then place the granulated mixture in a graphitization furnace, and obtain artificial graphite material after high-temperature graphitization;
[0014] Step (3) Preparation of asphalt-coated silicon-carbon composite particles
[0015] The artificial graphite of step (2) is mixed with the silicon material, and then the asphalt of step (1) is added. After adding a certain amount of anhydrous ethanol, a planetary ball mill is used for wet mixing. The mixed material is poured into a beaker and dried in a blast drying oven to obtain a silicon-carbon composite precursor. The material is pre-carbonized in an argon atmosphere, and then carbonized at a high temperature. The carbonized material is ground and sieved to obtain asphalt-coated silicon-carbon composite particles;
[0016] Step (4) Preparation of carbon nanotube conductive agent
[0017] The silicon substrate with the catalyst system is placed in a tube furnace, Ar is introduced, the quartz tube is cleaned, and hydrogen is introduced while the temperature is raised. As the temperature gradually rises, the iron film is slowly cracked. The temperature is raised and annealed for a certain time. The iron film is cracked into iron nanoparticles of uniform size. Then, under a certain atmosphere and controlled time, a carbon nanotube conductive agent is prepared. After natural cooling, the product is taken out and mechanically peeled off.
[0018] Step (5) Preparation of glucose-based hard carbon precursor
[0019] Glucose and water are mixed to obtain a glucose solution, and then the glucose solution and water are added into a stainless steel high-pressure reactor, and after hydrothermal reaction at a certain temperature, the mixture is naturally cooled to room temperature, washed with deionized water and filtered to neutrality, and the obtained solid precipitate is dried in a forced air drying oven to obtain a glucose-based hard carbon precursor;
[0020] Step (6) Preparation of silicon-carbon composite fast-charging negative electrode material
[0021] The glucose-based hard carbon precursor of step (5) is added to the asphalt-coated silicon-carbon composite material of step (3) for coating, and finally the carbon nanotube conductive agent of step (4) is added and sintered in a tube furnace (after heating, the precursor is pre-carbonized at medium and low temperature, then heated, kept warm, ground and sieved to obtain a silicon-carbon composite fast-charging negative electrode material.
[0022] Preferably, in step (1), the preparation of mesophase asphalt is
[0023] After the raw asphalt is ground and crushed, a thermal conversion experiment is carried out in a stainless steel high-temperature and high-pressure reactor equipped with a temperature controller. The heating rate is 5-8°C / min, and the autogenous pressure is generated under the protection of N2 atmosphere. With stirring, the temperature is kept constant at a predetermined temperature of 385°C-445°C for 2-10 hours, the system pressure is discharged, and the temperature is naturally cooled to room temperature to obtain the intermediate phase asphalt.
[0024] The advantage of the present invention is that the mesophase asphalt is prepared by thermal polymerization using purified coal tar as raw material, which greatly shortens the time of mesophase conversion. The thermal polymerization time has a great influence on the optical structure of the mesophase asphalt. As time goes by, the mesophase continues to merge.
[0025] Preferably, step (2) preparation of artificial graphite material
[0026] Take 300-400 g of needle coke powder, add the intermediate phase (mass fraction of 0-20%) of step (1) thereto, mix the two thoroughly in a mixer, stir for 1-2 h, and at a frequency of 50-100 Hz. Place the mixture in a homemade converter for granulation under the protection of 0.1-0.3 L / min N2, and at a converter frequency of 20-30 Hz. Heat the mixture to 650-700°C at a heating rate of 3-5°C / min. Place the granulated mixture in a graphitization furnace, and graphitize it at a high temperature of 2800-3000°C to obtain an artificial graphite material.
[0027] The advantage of adopting the present invention is that needle coke powder and binder asphalt powder are mixed, and after granulation and graphitization treatment, a secondary particle artificial graphite negative electrode material is obtained. The particle size and tap density of the artificial graphite negative electrode material prepared under this condition are significantly improved, and finally a secondary particle artificial graphite negative electrode material is prepared, which retains the high capacity advantage of the primary particle negative electrode material and makes up for the deficiency of the primary particle in rate performance, so that high added value utilization of coal tar can be realized, and excellent high rate charge and discharge capability is also shown in rate performance test.
[0028] Preferably, in step (3), the preparation of asphalt-coated silicon-carbon composite particles
[0029] Take 36-42 g of the artificial graphite of step (2) and 4-6 g of silicon material and mix them, then add the asphalt of step (1), add anhydrous ethanol, use a planetary ball mill to wet mix for 5-6 hours, pour the mixed material into a beaker and dry it in a forced air drying oven to obtain a silicon-carbon composite precursor, use an argon atmosphere, 300-1200° C. for pre-carbonization for 3-4 hours, then heat up and carbonize for 6-7 hours, grind the carbonized material through a 300-350 mesh sieve to obtain asphalt-coated silicon-carbon composite particles.
[0030] The advantage of adopting the present invention is that by using asphalt as the coating material and low-temperature carbonization, effective coating of silicon-carbon composite particles is achieved. The design of the multi-level coating structure not only improves the cycle stability of the material, but also optimizes its electrochemical performance. At the same time, the asphalt carbon coating can reduce the direct contact between silicon nanoparticles and the electrolyte, thereby reducing the generation of side reactions and reducing the consumption of the electrolyte.
[0031] Preferably, in step (4), the preparation of the carbon nanotube conductive agent
[0032] The silicon substrate with the catalyst system is placed in a tubular furnace, 1000-1200sccm Ar is introduced, the quartz tube is cleaned for 10-20 minutes, and hydrogen is introduced while the temperature starts to rise. As the temperature gradually rises, the iron film is slowly cracked. The temperature rises to 750-800°C, annealing is performed for 5-10 minutes, and the iron film is cracked into iron nanoparticles of uniform size. Then, the carbon nanotube conductive agent is prepared under a moisture value of 150-180ppm, an ethylene flow rate of 100-120sccm, and a hydrogen flow rate of 700-750sccm for a controlled time of 5-30 minutes. The product is taken out after natural cooling and mechanically peeled off.
[0033] The advantages of adopting the present invention are that the present invention uses water-assisted chemical vapor deposition (CVD) to achieve directional and positioned growth of carbon nanotube arrays, and the array structure is highly ordered, has high stability and excellent mechanical and electrical properties, and the water-assisted chemical vapor deposition method has lower energy consumption and less environmental pollution, which is conducive to promoting the green preparation and sustainable development of carbon nanotube conductive agents.
[0034] Preferably, in step (5), preparation of a glucose-based hard carbon precursor
[0035] 2.5-3 g of glucose and 7.5-8 g of water were mixed to obtain a 25-26% glucose solution, and then the 25-26% glucose solution and 56.67-72.12 g were added into a stainless steel high-pressure reactor, and hydrothermally reacted at 240-280° C. for 4-5 h, naturally cooled to room temperature, washed with deionized water and filtered to neutrality, and the obtained solid precipitate was dried in a forced air drying oven for 24-26 h to obtain a glucose-based hard carbon precursor.
[0036] The advantages of the present invention are that the present invention adopts a hydrothermal method to prepare a glucose-based hard carbon precursor. Compared with the traditional method, the present invention has a faster reaction rate, so that the reaction time is shortened, the experimental equipment only requires a simple reactor, the process is easy to control, glucose is a biomass model compound, the price is low, the molecule contains highly active hydroxyl groups, and the temperature at which the hydrothermal reaction occurs is relatively low.
[0037] Preferably, step (6) preparation of silicon-carbon composite fast-charging negative electrode material
[0038] The glucose-based hard carbon precursor of step (5) (the added amount is 10-12% of the mass of the asphalt-coated silicon-carbon composite particles) is added to the asphalt-coated silicon-carbon composite material of step (3) for coating, and finally the carbon nanotube conductive agent of step (4) is added and sintered in a tubular furnace (after heating to 350-400°C, the precursor is pre-carbonized at medium and low temperature for 3-4 hours, then heated to 700-750°C and kept warm for 6-7 hours), ground and sieved to obtain a silicon-carbon composite fast-charging negative electrode material.
[0039] The advantage of adopting the present invention is that the present invention adopts silicon, artificial graphite and monohydrated glucose as raw materials, and prepares silicon-carbon negative electrode material by high-temperature pyrolysis method. After the silicon-carbon negative electrode material is evenly mixed with asphalt of different contents, it is subjected to high-temperature carbonization treatment to obtain a composite negative electrode material. The thin carbon layer on the surface of the obtained composite material after carbonization can improve the conductivity of the material, and to a certain extent can alleviate the volume expansion of the material, which is helpful to improve the charging and discharging performance of the silicon-carbon material, and finally a more stable silicon-carbon composite fast-charging negative electrode material with excellent rate performance is obtained.
[0040] In summary, the present invention has the following beneficial effects:
[0041] 1. The advantage of the present invention is that the mesophase asphalt is prepared by thermal polymerization using purified coal tar as raw material, which greatly shortens the time of mesophase conversion. The thermal polymerization time has a great influence on the optical structure of the mesophase asphalt. As time goes by, the mesophase continues to merge.
[0042] 2. The advantage of the present invention is that needle coke powder and binder asphalt powder are mixed, and after granulation and graphitization treatment, a secondary particle artificial graphite negative electrode material is obtained. The particle size and tap density of the artificial graphite negative electrode material prepared under this condition are significantly improved, and finally a secondary particle artificial graphite negative electrode material is prepared, which retains the high capacity advantage of the primary particle negative electrode material and makes up for the deficiency of the primary particle in rate performance, thereby realizing high added value utilization of coal tar pitch and also showing excellent high rate charge and discharge capability in rate performance test.
[0043] 3. The advantage of the present invention is that by using asphalt as the coating material and low-temperature carbonization, effective coating of silicon-carbon composite particles is achieved. The design of the multi-level coating structure not only improves the cycle stability of the material, but also optimizes its electrochemical properties. At the same time, the asphalt carbon coating can reduce the direct contact between silicon nanoparticles and the electrolyte, thereby reducing the generation of side reactions and reducing the consumption of electrolyte.
[0044] 4. The advantage of adopting the present invention is that the present invention uses water-assisted chemical vapor deposition (CVD) to achieve directional and positioned growth of carbon nanotube arrays, and the array structure is highly ordered, with high stability and excellent mechanical and electrical properties. In addition, the water-assisted chemical vapor deposition method has lower energy consumption and less environmental pollution, which is conducive to promoting the green preparation and sustainable development of carbon nanotube conductive agents.
[0045] 5. The advantages of the present invention are that the present invention adopts a hydrothermal method to prepare a glucose-based hard carbon precursor. Compared with the traditional method, it has a faster reaction rate, so that the reaction time is shortened, the test equipment only requires a simple reactor, the process is easy to control, glucose is a biomass model compound, the price is low, the molecule contains highly active hydroxyl groups, and the temperature at which the hydrothermal reaction occurs is relatively low.
[0046] 6. The advantage of adopting the present invention is that the present invention adopts silicon, artificial graphite and monohydrated glucose as raw materials, and prepares silicon-carbon negative electrode material by high-temperature pyrolysis method. After the silicon-carbon negative electrode material is evenly mixed with asphalt of different contents, it is subjected to high-temperature carbonization treatment to obtain a composite negative electrode material. The thin carbon layer on the surface of the obtained composite material after carbonization can improve the conductivity of the material, and to a certain extent can alleviate the volume expansion of the material, which is helpful to improve the charge and discharge performance of the silicon-carbon material, and finally a more stable silicon-carbon composite fast-charging negative electrode material with excellent rate performance is obtained. BRIEF DESCRIPTION OF THE DRAWINGS
[0047] Figure 1 is the XRD pattern of Example 2 of the present invention;
[0048] Figure 2 is a SEM image of Example 2 of the present invention;
[0049] Figure 3 is a charge and discharge curve diagram of Example 2 of the present invention;
[0050] Figure 4 This is a rate performance diagram of an embodiment of a preparation process of a fast-charging negative electrode material of the present invention;
[0051] Figure 5 It is a process flow chart of the preparation of a fast-charging negative electrode material of the present invention. DETAILED DESCRIPTION
[0052] The following examples are used to illustrate the present invention, but are not intended to limit the scope of the present invention. Without departing from the spirit and substance of the present invention, modifications or substitutions made to the methods, steps or conditions of the present invention are within the scope of the present invention.
[0053] If not otherwise specified, the technical means used in the examples are conventional means known to those skilled in the art. In addition, all the raw materials used in the examples are known commercial products.
[0054] Example 1
[0055] Step (1) Preparation of mesophase pitch
[0056] After the raw asphalt is ground and crushed, a thermal conversion experiment is carried out in a stainless steel high-temperature and high-pressure reactor equipped with a temperature controller, with a heating rate of 5°C / min, autogenerated pressure under N2 atmosphere protection, stirring, and constant temperature of 385°C for 2h, the system pressure is discharged, and the temperature is naturally cooled to room temperature to obtain the intermediate phase asphalt;
[0057] Step (2) Preparation of artificial graphite material
[0058] Take 300 g of needle coke powder, add the mesophase pitch (mass fraction of 1%) of step (1) thereto, mix the two thoroughly in a mixer, stir for 1 h, and at a frequency of 50 Hz. Place the mixture in a homemade converter for granulation under the protection of 0.1 L / min N2, and at a converter frequency of 20 Hz. Heat the temperature to 650°C at a heating rate of 3°C / min. Place the granulated mixture in a graphitization furnace, and graphitize it at 2800°C to obtain an artificial graphite material.
[0059] Step (3) Preparation of asphalt-coated silicon-carbon composite particles
[0060] 36 g of the artificial graphite prepared in step (2) was mixed with 4 g of silicon material, and then the asphalt prepared in step (1) was added. After adding anhydrous ethanol, the mixture was wet-mixed for 5 h using a planetary ball mill. The mixed material was poured into a beaker and dried in a forced air drying oven to obtain a silicon-carbon composite precursor. The precursor was pre-carbonized at 1000° C. for 3 h in an argon atmosphere and then carbonized for 6 h at a higher temperature. The carbonized material was ground through a 300-mesh sieve to obtain asphalt-coated silicon-carbon composite particles.
[0061] Step (4) Preparation of carbon nanotube conductive agent
[0062] The silicon substrate with the catalyst system was placed in a tube furnace, 1000 sccm Ar was introduced, the quartz tube was cleaned for 10 minutes, and hydrogen was introduced while the temperature was raised. As the temperature gradually increased, the iron film was slowly cracked. The temperature was raised to 750°C, annealed for 5 minutes, and the iron film was cracked into iron nanoparticles of uniform size. Then, the carbon nanotube conductive agent was prepared at a moisture value of 150 ppm, an ethylene flow rate of 100 sccm, and a hydrogen flow rate of 700 sccm for a controlled time of 5 minutes. After natural cooling, the product was taken out and mechanically peeled off.
[0063] Step (5) Preparation of glucose-based hard carbon precursor
[0064] 2.5 g of glucose and 7.5 g of water were mixed to obtain a 25% glucose solution, and then the 25-26% glucose solution and 56.67 g of water were added to a stainless steel autoclave for hydrothermal reaction at 240 ° C for 4 h, naturally cooled to room temperature, washed with deionized water and filtered to neutrality, and the obtained solid precipitate was dried in a forced air drying oven for 24 h to obtain a glucose-based hard carbon precursor;
[0065] Step (6) Preparation of silicon-carbon composite fast-charging negative electrode material
[0066] The glucose-based hard carbon precursor of step (5) (the added amount is 10% of the mass of the asphalt-coated silicon-carbon composite particles) is added to the asphalt-coated silicon-carbon composite material of step (3) for coating, and finally the carbon nanotube conductive agent of step (4) is added and sintered in a tubular furnace (after heating to 350°C, the precursor is pre-carbonized at medium and low temperature for 3 hours, then heated to 700°C and kept warm for 6 hours), ground and sieved to obtain a silicon-carbon composite fast-charging negative electrode material.
[0067] Example 2
[0068] Step (1) Preparation of mesophase pitch
[0069] After the raw asphalt is ground and crushed, a thermal conversion experiment is carried out in a stainless steel high-temperature and high-pressure reactor equipped with a temperature controller, with a heating rate of 5°C / min, autogenerated pressure under N2 atmosphere protection, stirring, and constant temperature of 385°C for 2h, the system pressure is discharged, and the temperature is naturally cooled to room temperature to obtain the intermediate phase asphalt;
[0070] Step (2) Preparation of artificial graphite material
[0071] Take 300 g of needle coke powder, add the mesophase pitch (mass fraction of 8%) of step (1) thereto, mix the two thoroughly in a mixer, stir for 1 h, and at a frequency of 50 Hz. Place the mixture in a homemade converter for granulation under the protection of 0.1 L / min N2, and at a converter frequency of 20 Hz. Heat the temperature to 650°C at a heating rate of 3°C / min. Place the granulated mixture in a graphitization furnace, and graphitize it at a high temperature of 2800°C to obtain an artificial graphite material.
[0072] Step (3) Preparation of asphalt-coated silicon-carbon composite particles
[0073] 36 g of the artificial graphite prepared in step (2) was mixed with 4 g of silicon material, and then the asphalt prepared in step (1) was added. After adding anhydrous ethanol, the mixture was wet-mixed for 5 h using a planetary ball mill. The mixed material was poured into a beaker and dried in a forced air drying oven to obtain a silicon-carbon composite precursor. The precursor was pre-carbonized at 1000° C. for 3 h in an argon atmosphere and then carbonized for 6 h at a higher temperature. The carbonized material was ground through a 300-mesh sieve to obtain asphalt-coated silicon-carbon composite particles.
[0074] Step (4) Preparation of carbon nanotube conductive agent
[0075] The silicon substrate with the catalyst system was placed in a tube furnace, 1000 sccm Ar was introduced, the quartz tube was cleaned for 10 minutes, and hydrogen was introduced while the temperature was raised. As the temperature gradually increased, the iron film was slowly cracked. The temperature was raised to 750°C, annealed for 5 minutes, and the iron film was cracked into iron nanoparticles of uniform size. Then, the carbon nanotube conductive agent was prepared at a moisture value of 150 ppm, an ethylene flow rate of 100 sccm, and a hydrogen flow rate of 700 sccm for a controlled time of 5 minutes. After natural cooling, the product was taken out and mechanically peeled off.
[0076] Step (5) Preparation of glucose-based hard carbon precursor
[0077] 2.5 g of glucose and 7.5 g of water were mixed to obtain a 25% glucose solution, and the 25% glucose solution and 56.67 g of water were added to a stainless steel autoclave for hydrothermal reaction at 240 ° C for 4 h, naturally cooled to room temperature, washed with deionized water and filtered to neutrality, and the obtained solid precipitate was dried in a forced air drying oven for 24 h to obtain a glucose-based hard carbon precursor;
[0078] Step (6) Preparation of silicon-carbon composite fast-charging negative electrode material
[0079] The glucose-based hard carbon precursor of step (5) (the added amount is 10% of the mass of the asphalt-coated silicon-carbon composite particles) is added to the asphalt-coated silicon-carbon composite material of step (3) for coating, and finally the carbon nanotube conductive agent of step (4) is added and sintered in a tubular furnace (after heating to 350°C, the precursor is pre-carbonized at medium and low temperature for 3 hours, then heated to 700°C and kept warm for 6 hours), ground and sieved to obtain a silicon-carbon composite fast-charging negative electrode material.
[0080] The XRD pattern of the prepared silicon-carbon composite fast-charge negative electrode material is shown in Figure 2. Figure 1 As shown in the figure, it can be seen that a characteristic diffraction peak appears at 26.39, corresponding to the (111) crystal plane of silicon. Figure 2 This is an SEM image of a silicon-carbon composite fast-charging negative electrode material. From the image, we can see that its microstructure is granular, and the surface of the particles is relatively smooth due to the coating effect.
[0081] from Figure 3In the charge and discharge curve, we can see that the reversible capacity of the prepared silicon-carbon composite fast-charge negative electrode material reaches 480.53mAh / g. Combined with Table 1, the charge and discharge specific capacity of Example 2 is the best, and the comparative example 2 is relatively poor. Its reversible specific capacity shows an overall trend of first rising and then falling. When the carbonization temperature is 1000°C, its electrochemical performance is better. As the heat treatment temperature increases, the interface resistance of the material continues to decrease. When the heat treatment temperature is 1000°C, the interface resistance reaches the minimum, and continues to increase when the temperature continues to rise. Therefore, the material obtained by heat treatment at 1000°C has the best charge and discharge specific capacity performance, which has huge advantages in the field of fast-charge negative electrode materials.
[0082] from Figure 4 In the rate performance diagram, combined with Table 2, it can be seen that the electrochemical performance of Example 2 is the best. Compared with Comparative Example 2, the performance of Comparative Example 2 is poor. It can be concluded that the mass fraction of asphalt added to the artificial graphite material is most appropriate at 8%. Continuing to increase or decrease it will only lead to a deterioration in the specific capacity. At this time, the secondary particles formed by the granulation process have better performance, which improves the tap density of the negative electrode material, and has an optimal specific capacity that improves the specific capacity of the negative electrode material, maximizing the advantage of large particles with high capacity, and has great potential in the preparation of composite negative electrode materials.
[0083] Example 3
[0084] Step (1) Preparation of mesophase pitch
[0085] After the raw asphalt is ground and crushed, a thermal conversion experiment is carried out in a stainless steel high-temperature and high-pressure reactor equipped with a temperature controller, with a heating rate of 5°C / min, autogenerated pressure under N2 atmosphere protection, stirring, and constant temperature of 385°C for 2h, the system pressure is discharged, and the temperature is naturally cooled to room temperature to obtain the intermediate phase asphalt;
[0086] Step (2) Preparation of artificial graphite material
[0087] Take 300 g of needle coke powder, add the mesophase pitch (mass fraction of 10%) of step (1) thereto, mix the two thoroughly in a mixer, stir for 1 h, and at a frequency of 50 Hz. Place the mixture in a homemade converter under the protection of 0.1 L / min N2 for granulation. The converter frequency is 20 Hz, and the temperature is raised to 650°C at a heating rate of 3°C / min. Place the granulated mixture in a graphitization furnace, and obtain artificial graphite material after high-temperature graphitization at 2800°C.
[0088] Step (3) Preparation of asphalt-coated silicon-carbon composite particles
[0089] 36 g of the artificial graphite prepared in step (2) was mixed with 4 g of silicon material, and then the asphalt prepared in step (1) was added. After adding anhydrous ethanol, the mixture was wet-mixed for 5 h using a planetary ball mill. The mixed material was poured into a beaker and dried in a forced air drying oven to obtain a silicon-carbon composite precursor. The precursor was pre-carbonized at 1000° C. for 3 h in an argon atmosphere and then carbonized for 6 h at a higher temperature. The carbonized material was ground through a 300-mesh sieve to obtain asphalt-coated silicon-carbon composite particles.
[0090] Step (4) Preparation of carbon nanotube conductive agent
[0091] The silicon substrate with the catalyst system was placed in a tube furnace, 1000 sccm Ar was introduced, the quartz tube was cleaned for 10 minutes, and hydrogen was introduced while the temperature was raised. As the temperature gradually increased, the iron film was slowly cracked. The temperature was raised to 750°C, annealed for 5 minutes, and the iron film was cracked into iron nanoparticles of uniform size. Then, the carbon nanotube conductive agent was prepared at a moisture value of 150 ppm, an ethylene flow rate of 100 sccm, and a hydrogen flow rate of 700 sccm for a controlled time of 5 minutes. After natural cooling, the product was taken out and mechanically peeled off.
[0092] Step (5) Preparation of glucose-based hard carbon precursor
[0093] 2.5 g of glucose and 7.5 g of water were mixed to obtain a 25% glucose solution, and the 25% glucose solution and 56.67 g of water were added to a stainless steel autoclave for hydrothermal reaction at 240 ° C for 4 h, naturally cooled to room temperature, washed with deionized water and filtered to neutrality, and the obtained solid precipitate was dried in a forced air drying oven for 24 h to obtain a glucose-based hard carbon precursor;
[0094] Step (6) Preparation of silicon-carbon composite fast-charging negative electrode material
[0095] The glucose-based hard carbon precursor of step (5) (the added amount is 10% of the mass of the asphalt-coated silicon-carbon composite particles) is added to the asphalt-coated silicon-carbon composite material of step (3) for coating, and finally the carbon nanotube conductive agent of step (4) is added and sintered in a tubular furnace (after heating to 350°C, the precursor is pre-carbonized at medium and low temperature for 3 hours, then heated to 700°C and kept warm for 6 hours), ground and sieved to obtain a silicon-carbon composite fast-charging negative electrode material.
[0096] Example 4
[0097] Step (1) Preparation of mesophase pitch
[0098] After the raw asphalt is ground and crushed, a thermal conversion experiment is carried out in a stainless steel high-temperature and high-pressure reactor equipped with a temperature controller, with a heating rate of 5°C / min, autogenerated pressure under N2 atmosphere protection, stirring, and constant temperature of 385°C for 2h, the system pressure is discharged, and the temperature is naturally cooled to room temperature to obtain the intermediate phase asphalt;
[0099] Step (2) Preparation of artificial graphite material
[0100] Take 300 g of needle coke powder, add the mesophase pitch (mass fraction of 8%) of step (1) thereto, mix the two thoroughly in a mixer, stir for 1 h, and at a frequency of 50 Hz. Place the mixture in a homemade converter for granulation under the protection of 0.1 L / min N2, and at a converter frequency of 20 Hz. Heat the temperature to 650°C at a heating rate of 3°C / min. Place the granulated mixture in a graphitization furnace, and graphitize it at 2800°C to obtain an artificial graphite material.
[0101] Step (3) Preparation of asphalt-coated silicon-carbon composite particles
[0102] 36 g of the artificial graphite prepared in step (2) was mixed with 4 g of silicon material, and then the asphalt prepared in step (1) was added. After adding anhydrous ethanol, the mixture was wet-mixed for 5 h using a planetary ball mill. The mixed material was poured into a beaker and dried in a forced air drying oven to obtain a silicon-carbon composite precursor. The mixture was pre-carbonized at 900° C. for 3 h in an argon atmosphere and then carbonized at a high temperature for 6 h. The carbonized material was ground through a 300-mesh sieve to obtain asphalt-coated silicon-carbon composite particles.
[0103] Step (4) Preparation of carbon nanotube conductive agent
[0104] The silicon substrate with the catalyst system was placed in a tube furnace, 1000 sccm Ar was introduced, the quartz tube was cleaned for 10 minutes, and hydrogen was introduced while the temperature was raised. As the temperature gradually increased, the iron film was slowly cracked. The temperature was raised to 750°C, annealed for 5 minutes, and the iron film was cracked into iron nanoparticles of uniform size. Then, the carbon nanotube conductive agent was prepared at a moisture value of 150 ppm, an ethylene flow rate of 100 sccm, and a hydrogen flow rate of 700 sccm for a controlled time of 5 minutes. After natural cooling, the product was taken out and mechanically peeled off.
[0105] Step (5) Preparation of glucose-based hard carbon precursor
[0106] 2.5 g of glucose and 7.5 g of water were mixed to obtain a 25% glucose solution, and the 25% glucose solution and 56.67 g of water were added to a stainless steel autoclave for hydrothermal reaction at 240 ° C for 4 to 5 hours, and then naturally cooled to room temperature, washed with deionized water and filtered to neutrality, and the obtained solid precipitate was dried in a forced air drying oven for 24 hours to obtain a glucose-based hard carbon precursor;
[0107] Step (6) Preparation of silicon-carbon composite fast-charging negative electrode material
[0108] The glucose-based hard carbon precursor of step (5) (the added amount is 10% of the mass of the asphalt-coated silicon-carbon composite particles) is added to the asphalt-coated silicon-carbon composite material of step (3) for coating, and finally the carbon nanotube conductive agent of step (4) is added and sintered in a tubular furnace (after heating to 350°C, the precursor is pre-carbonized at medium and low temperature for 3 hours, then heated to 700°C and kept warm for 6 hours), ground and sieved to obtain a silicon-carbon composite fast-charging negative electrode material.
[0109] Example 5
[0110] Step (1) Preparation of mesophase pitch
[0111] After the raw asphalt is ground and crushed, a thermal conversion experiment is carried out in a stainless steel high-temperature and high-pressure reactor equipped with a temperature controller, with a heating rate of 5°C / min, autogenerated pressure under N2 atmosphere protection, stirring, and constant temperature of 385°C for 2h, the system pressure is discharged, and the temperature is naturally cooled to room temperature to obtain the intermediate phase asphalt;
[0112] Step (2) Preparation of artificial graphite material
[0113] Take 300 g of needle coke powder, add the mesophase pitch (mass fraction of 8%) of step (1) thereto, mix the two thoroughly in a mixer, stir for 1 h, and at a frequency of 50 Hz. Place the mixture in a homemade converter for granulation under the protection of 0.1 L / min N2, and at a converter frequency of 20 Hz. Heat the temperature to 650°C at a heating rate of 3°C / min. Place the granulated mixture in a graphitization furnace, and graphitize it at 2800°C to obtain an artificial graphite material.
[0114] Step (3) Preparation of asphalt-coated silicon-carbon composite particles
[0115] 36 g of the artificial graphite prepared in step (2) was mixed with 4 g of silicon material, and then the asphalt prepared in step (1) was added. After adding anhydrous ethanol, the mixture was wet-mixed for 5 h using a planetary ball mill. The mixed material was poured into a beaker and dried in a forced air drying oven to obtain a silicon-carbon composite precursor. The mixture was pre-carbonized at 1100° C. for 3 h in an argon atmosphere and then carbonized for 6 h at a higher temperature. The carbonized material was ground through a 300-mesh sieve to obtain asphalt-coated silicon-carbon composite particles.
[0116] Step (4) Preparation of carbon nanotube conductive agent
[0117] The silicon substrate with the catalyst system was placed in a tube furnace, 1000 sccm Ar was introduced, the quartz tube was cleaned for 10 minutes, and hydrogen was introduced while the temperature was raised. As the temperature gradually increased, the iron film was slowly cracked. The temperature was raised to 750°C, annealed for 5 minutes, and the iron film was cracked into iron nanoparticles of uniform size. Then, the carbon nanotube conductive agent was prepared at a moisture value of 150 ppm, an ethylene flow rate of 100 sccm, and a hydrogen flow rate of 700 sccm for a controlled time of 5 minutes. After natural cooling, the product was taken out and mechanically peeled off.
[0118] Step (5) Preparation of glucose-based hard carbon precursor
[0119] 2.5 g of glucose and 7.5 g of water were mixed to obtain a 25% glucose solution, and the 25% glucose solution and 56.67 g of water were added to a stainless steel autoclave for hydrothermal reaction at 240 ° C for 4 to 5 hours, and then naturally cooled to room temperature, washed with deionized water and filtered to neutrality, and the obtained solid precipitate was dried in a forced air drying oven for 24 hours to obtain a glucose-based hard carbon precursor;
[0120] Step (6) Preparation of silicon-carbon composite fast-charging negative electrode material
[0121] The glucose-based hard carbon precursor of step (5) (the added amount is 10% of the mass of the asphalt-coated silicon-carbon composite particles) is added to the asphalt-coated silicon-carbon composite material of step (3) for coating, and finally the carbon nanotube conductive agent of step (4) is added and sintered in a tubular furnace (after heating to 350°C, the precursor is pre-carbonized at medium and low temperature for 3 hours, then heated to 700°C and kept warm for 6 hours), ground and sieved to obtain a silicon-carbon composite fast-charging negative electrode material.
[0122] Comparative Example 1
[0123] Step (1) Preparation of artificial graphite material
[0124] Take 300g of needle coke powder, add mesophase pitch (mass fraction of 5%) into it, mix the two thoroughly in a mixer, stir for 1h, frequency of 50Hz, place the mixture in a homemade converter for granulation under 0.1L / minN2 protection, converter frequency of 20Hz, heat to 650℃ at a heating rate of 3℃ / min, then place the granulated mixture in a graphitization furnace, and obtain artificial graphite material after high temperature graphitization at 2800℃;
[0125] Step (2) Preparation of asphalt-coated silicon-carbon composite particles
[0126] 36 g of the artificial graphite prepared in step (1) was mixed with 4 g of silicon material, and then asphalt was added. After adding anhydrous ethanol, the mixture was wet-mixed for 5 h using a planetary ball mill. The mixed material was poured into a beaker and dried in a blast drying oven to obtain a silicon-carbon composite precursor. The precursor was pre-carbonized at 1000° C. for 3 h in an argon atmosphere, and then carbonized at a high temperature for 6 h. The carbonized material was ground through a 300-mesh sieve to obtain asphalt-coated silicon-carbon composite particles.
[0127] Step (3) Preparation of carbon nanotube conductive agent
[0128] The silicon substrate with the catalyst system was placed in a tube furnace, 1000 sccm Ar was introduced, the quartz tube was cleaned for 10 minutes, and hydrogen was introduced while the temperature was raised. As the temperature gradually increased, the iron film was slowly cracked. The temperature was raised to 750°C, annealed for 5 minutes, and the iron film was cracked into iron nanoparticles of uniform size. Then, the carbon nanotube conductive agent was prepared at a moisture value of 150 ppm, an ethylene flow rate of 100 sccm, and a hydrogen flow rate of 700 sccm for a controlled time of 5 minutes. After natural cooling, the product was taken out and mechanically peeled off.
[0129] Step (4) Preparation of glucose-based hard carbon precursor
[0130] 2.5 g of glucose and 7.5 g of water were mixed to obtain a 25% glucose solution, and the 25% glucose solution and 56.67 g of water were added to a stainless steel autoclave for hydrothermal reaction at 240 ° C for 4 h, and naturally cooled to room temperature, washed with deionized water and filtered to neutrality, and the obtained solid precipitate was dried in a forced air drying oven for 24 h to obtain a glucose-based hard carbon precursor;
[0131] Step (5) Preparation of silicon-carbon composite fast-charging negative electrode material
[0132] The glucose-based hard carbon precursor of step (4) (the added amount is 10% of the mass of the asphalt-coated silicon-carbon composite particles) is added to the asphalt-coated silicon-carbon composite material of step (2) for coating, and finally the carbon nanotube conductive agent of step (3) is added and sintered in a tubular furnace (after heating to 350°C, the precursor is pre-carbonized at medium and low temperature for 3 hours, then heated to 700°C and kept warm for 6 hours), ground and sieved to obtain a silicon-carbon composite fast-charging negative electrode material.
[0133] Comparative Example 2
[0134] Step (1) Preparation of mesophase pitch
[0135] After the raw asphalt is ground and crushed, a thermal conversion experiment is carried out in a stainless steel high-temperature and high-pressure reactor equipped with a temperature controller, with a heating rate of 5°C / min, autogenerated pressure under N2 atmosphere protection, stirring, and constant temperature of 385°C for 2h, the system pressure is discharged, and the temperature is naturally cooled to room temperature to obtain the intermediate phase asphalt;
[0136] Step (2) Preparation of artificial graphite material
[0137] Take 300 g of needle coke powder, add the mesophase pitch (mass fraction of 12%) of step (1) thereto, mix the two thoroughly in a mixer, stir for 1 h, and at a frequency of 50 Hz. Place the mixture in a homemade converter for granulation under the protection of 0.1 L / min N2, and at a converter frequency of 20 Hz. Heat the temperature to 650°C at a heating rate of 3°C / min. Place the granulated mixture in a graphitization furnace, and graphitize it at a high temperature of 2800°C to obtain an artificial graphite material.
[0138] Step (3) Preparation of asphalt-coated silicon-carbon composite particles
[0139] 36 g of the artificial graphite prepared in step (2) was mixed with 4 g of silicon material, and then the asphalt prepared in step (1) was added. After adding anhydrous ethanol, the mixture was wet-mixed for 5 h using a planetary ball mill. The mixed material was poured into a beaker and dried in a forced air drying oven to obtain a silicon-carbon composite precursor. The mixture was pre-carbonized at 1200° C. for 3 h in an argon atmosphere and then carbonized for 6 h at a higher temperature. The carbonized material was ground through a 300-mesh sieve to obtain asphalt-coated silicon-carbon composite particles.
[0140] Step (4) Preparation of glucose-based hard carbon precursor
[0141] 2.5 g of glucose and 7.5 g of water were mixed to obtain a 25% glucose solution, and the 25% glucose solution and 56.67 g of water were added to a stainless steel autoclave for hydrothermal reaction at 240 ° C for 4 to 5 hours, and then naturally cooled to room temperature, washed with deionized water and filtered to neutrality, and the obtained solid precipitate was dried in a forced air drying oven for 24 hours to obtain a glucose-based hard carbon precursor;
[0142] Step (5) Preparation of silicon-carbon composite fast-charging negative electrode material
[0143] The glucose-based hard carbon precursor of step (5) is added to the asphalt-coated silicon-carbon composite material of step (3) (the addition amount is 10% of the mass of the asphalt-coated silicon-carbon composite particles) for coating, and finally a carbon nanotube conductive agent is added and sintered in a tubular furnace (after heating to 350°C, the precursor is pre-carbonized at medium and low temperature for 3 hours, then heated to 700°C and kept warm for 6 hours), ground and sieved to obtain a silicon-carbon composite fast-charging negative electrode material.
[0144] Comparison of detection experiments:
[0145] The silicon-carbon composite fast-charging negative electrode materials obtained in Examples 1 to 5 and the comparative products 1 and 2 were tested, and the specific testing methods are as follows:
[0146] Charge and discharge test
[0147] The LAND battery test system was used to perform charge and discharge tests and rate performance tests on button lithium-ion batteries, with the discharge cut-off voltage set to 0.005V and the charge cut-off voltage set to 2V.
[0148] Electrochemical performance characterization
[0149] 1) After the button cell was aged for 12 h, it was used for the electrochemical performance test. The test equipment was the Xinwei battery performance tester. The specific test steps are as follows: constant current discharge conditions: 0.1C, cut-off voltage 0.005V, 0.05C, cut-off voltage 0.005V, 0.02C, cut-off voltage 0.005V, standstill: 5min, constant current charging conditions: 0.1C, cut-off voltage 2.0V, standstill: 5min, all tests were completed at 25℃;
[0150] 2) After the button cell has undergone the above test, it is subjected to rate performance test, and the test equipment is Xinwei battery performance tester. The specific test steps are as follows: constant current discharge: 0.1C, cut-off voltage 0.005V, standstill: 5min, constant current charging conditions: 0.1C, cut-off voltage 2.0V, standstill: 5min, repeat the charge and discharge rate from low to high, 0.2, 0.5, 1, 2C, all tests are completed at 25℃
[0151] This specific embodiment is merely an explanation of the present invention, and it is not a limitation of the present invention. A person skilled in the art can make non-creative modifications to the present embodiment as needed after reading this specification. However, as long as it is within the scope of the claims of the present invention, it is protected by the patent law.
[0152] Table 1 Initial charge and discharge specific capacity test results
[0153] Example Asphalt mass fraction / % Heat treatment temperature / ℃ <![CDATA[Discharge specific capacity / mAh·g -1 > <![CDATA[Charge specific capacity / mAh·g -1 > Coulomb efficiency / % 1 1 1000 550.06 461.72 83.94 2 8 1000 536.67 480.53 89.54 3 10 1000 543.39 475.25 87.46 4 8 900 553.20 473.82 85.65 5 8 1100 538.10 475.20 88.31 Comparative Example 1 5 1000 544.73 470.1 86.30 Comparative Example 2 12 1200 540.49 473.9 87.68
[0154] Table 2 Rate performance test results
[0155] Example Asphalt mass fraction / % Heat treatment temperature / ℃ <![CDATA[Charge specific capacity / mAh·g -1 > <![CDATA[0.2 C specific capacity / mAh·g -1 > 1 1 1000 461.72 325.65 2 8 1000 480.53 423.35 3 10 1000 475.25 410.71 4 8 900 473.82 405.02 5 8 1100 475.20 409.57 Comparative Example 1 5 1000 470.1 371.33 Comparative Example 2 12 1200 473.9 401.49
Claims
1. A process for preparing a fast-charging negative electrode material, characterized in that: include: Preparation of intermediate phase asphalt, preparation of artificial graphite materials, preparation of asphalt-coated silicon-carbon composite particles, preparation of carbon nanotube conductive agent, preparation of glucose-based hard carbon precursor, and preparation of silicon-carbon composite fast-charging negative electrode materials.
2. The process for preparing a fast-charging negative electrode material according to claim 1, characterized in that: Step (1) Preparation of mesophase pitch After the raw material asphalt is ground and crushed, a thermal conversion experiment is carried out in a stainless steel high-temperature and high-pressure reactor equipped with a temperature controller. Under the protection of N2 atmosphere, the system is pressurized, stirred, kept at a constant temperature for a certain period of time, the system pressure is discharged, and the system is naturally cooled to room temperature to obtain the intermediate phase asphalt. Step (2) Preparation of artificial graphite material Take needle coke powder, add the mesophase pitch of step (1) thereto, mix the two thoroughly and evenly in a mixer, stir for a certain time, set the frequency, place the mixture in a homemade converter under N2 protection for granulation, heat it to a specified temperature at a certain heating rate, then place the granulated mixture in a graphitization furnace, and obtain artificial graphite material after high-temperature graphitization; Step (3) Preparation of asphalt-coated silicon-carbon composite particles The artificial graphite of step (2) is mixed with the silicon material, and then the asphalt of step (1) is added. After adding a certain amount of anhydrous ethanol, a planetary ball mill is used for wet mixing. The mixed material is poured into a beaker and dried in a blast drying oven to obtain a silicon-carbon composite precursor. The material is pre-carbonized in an argon atmosphere, and then carbonized at a high temperature. The carbonized material is ground and sieved to obtain asphalt-coated silicon-carbon composite particles; Step (4) Preparation of carbon nanotube conductive agent The silicon substrate with the catalyst system is placed in a tube furnace, Ar is introduced, the quartz tube is cleaned, and hydrogen is introduced while the temperature is raised. As the temperature gradually rises, the iron film is slowly cracked. The temperature is raised and annealed for a certain time. The iron film is cracked into iron nanoparticles of uniform size. Then, under a certain atmosphere and controlled time, a carbon nanotube conductive agent is prepared. After natural cooling, the product is taken out and mechanically peeled off. Step (5) Preparation of glucose-based hard carbon precursor Glucose and water are mixed to obtain a glucose solution, and then the glucose solution and water are added into a stainless steel high-pressure reactor, and after hydrothermal reaction at a certain temperature, the mixture is naturally cooled to room temperature, washed with deionized water and filtered to neutrality, and the obtained solid precipitate is dried in a forced air drying oven to obtain a glucose-based hard carbon precursor; Step (6) Preparation of silicon-carbon composite fast-charging negative electrode material The glucose-based hard carbon precursor of step (5) is added to the asphalt-coated silicon-carbon composite material of step (3) for coating, and finally the carbon nanotube conductive agent of step (4) is added and sintered in a tubular furnace and heated. The precursor is pre-carbonized at medium and low temperatures, and then heated, kept warm, ground and sieved to obtain a silicon-carbon composite fast-charging negative electrode material.
3. The process for preparing a fast-charging negative electrode material according to claim 2, characterized in that: Step (1) Preparation of mesophase pitch After the raw asphalt is ground and crushed, a thermal conversion experiment is carried out in a stainless steel high-temperature and high-pressure reactor equipped with a temperature controller. The heating rate is 5-8°C / min, and the autogenous pressure is generated under the protection of N2 atmosphere. With stirring, the temperature is kept constant at a predetermined temperature of 385°C-445°C for 2-10 hours, the system pressure is discharged, and the temperature is naturally cooled to room temperature to obtain the intermediate phase asphalt.
4. The process for preparing a fast-charging negative electrode material according to claim 3, characterized in that: Step (2) Preparation of artificial graphite material Take 300-400 g of needle coke powder, add the mesophase pitch (mass fraction of 0-20%) of step (1) thereto, mix the two thoroughly in a mixer, stir for 1-2 h, and at a frequency of 50-100 Hz. Place the mixture in a homemade converter for granulation under the protection of 0.1-0.3 L / min N2, and at a converter frequency of 20-30 Hz. Heat the mixture to 650-700°C at a heating rate of 3-5°C / min. Place the granulated mixture in a graphitization furnace, and graphitize it at a high temperature of 2800-3000°C to obtain an artificial graphite material.
5. The process for preparing a fast-charging negative electrode material according to claim 4, characterized in that: Step (3) Preparation of asphalt-coated silicon-carbon composite particles Take 36-42 g of the artificial graphite of step (2) and 4-6 g of silicon material and mix them, then add the asphalt of step (1), add anhydrous ethanol, use a planetary ball mill to wet mix for 5-6 hours, pour the mixed material into a beaker and dry it in a forced air drying oven to obtain a silicon-carbon composite precursor, use an argon atmosphere, 300-1200° C. for pre-carbonization for 3-4 hours, then heat up and carbonize for 6-7 hours, grind the carbonized material through a 300-350 mesh sieve to obtain asphalt-coated silicon-carbon composite particles.
6. A process for preparing a fast-charging negative electrode material according to claim 5, characterized in that: Step (4) Preparation of carbon nanotube conductive agent The silicon substrate with the catalyst system is placed in a tubular furnace, 1000-1200sccm Ar is introduced, the quartz tube is cleaned for 10-20 minutes, and hydrogen is introduced while the temperature starts to rise. As the temperature gradually rises, the iron film is slowly cracked. The temperature rises to 750-800°C, annealing is performed for 5-10 minutes, and the iron film is cracked into iron nanoparticles of uniform size. Then, the carbon nanotube conductive agent is prepared under a moisture value of 150-180ppm, an ethylene flow rate of 100-120sccm, and a hydrogen flow rate of 700-750sccm for a controlled time of 5-30 minutes. The product is taken out after natural cooling and mechanically peeled off.
7. A process for preparing a fast-charging negative electrode material according to claim 6, characterized in that: Step (5) Preparation of glucose-based hard carbon precursor 2.5-3 g of glucose and 7.5-8 g of water were mixed to obtain a 25-26% glucose solution, and then the 25-26% glucose solution and 56.67-72.12 g of water were added to a stainless steel high-pressure reactor, and hydrothermally reacted at 240-280° C. for 4-5 hours, naturally cooled to room temperature, washed with deionized water and filtered to neutrality, and the obtained solid precipitate was dried in a forced air drying oven for 24-26 hours to obtain a glucose-based hard carbon precursor.
8. A process for preparing a fast-charging negative electrode material according to claim 7, characterized in that: Step (6) Preparation of silicon-carbon composite fast-charging negative electrode material The glucose-based hard carbon precursor of step (5) (the addition amount is 10-12% of the mass of the asphalt-coated silicon-carbon composite particles) is added to the asphalt-coated silicon-carbon composite material of step (3) for coating, and finally the carbon nanotube conductive agent of step (4) is added and sintered in a tubular furnace (after heating to 350-400°C, the precursor is pre-carbonized at medium and low temperature for 3-4 hours, then heated to 700-750°C and kept warm for 6-7 hours), ground and sieved to obtain a silicon-carbon composite fast-charging negative electrode material.
Citation Information
Patent Citations
High-energy silicon-carbon composite negative electrode material for lithium ion battery and manufacturing process thereof
CN101710617A
High-energy compound material used for cathode of lithium ion battery and process for preparing same
CN101841035A
Preparation method of power battery negative electrode material
CN112938959A
Negative active material and preparation method thereof, negative pole piece and lithium ion battery
CN115295780A
Preparation method of hard-soft carbon coated silicon carbon negative electrode material
CN119143109A